RAMP - risk analysis and management for projects : a strategic framework for managing project risk and its financial implications - Institution of Civil Engineers (United Kingdom).; Faculty of Actuaries in Scotland; Institute of Actuaries (United Kingdom). (London : Thomas Telford, 2005)
'This handbook shows how RAMP can enable one to identity, analyse and respond to risks, and place financial values on them. Allied with sound judgement, RAMP should reduce the chance of the resources committed to a project being wasted or the project being a failure. It should also lead to better financial returns for sponsors, investors and lenders, and help to improve the consequences of projects for the wider community. The handbook will be of use to everyone who is concerned with the financial, commercial, legal or engineering aspects of projects of any kind.''This is the second edition of the handbook and it incorporates some significant changes, with more attention being devoted to upside risks, general uncertainty, risk efficiency, decision criteria, and the need for independent validation of appraisals. There is also new material about public sector procurement. A new Appendix 12 presents recent evidence about the serious and sometimes unrecognised risks in major infrastructure projects, both in the UK and abroad, and makes recommendations for changes in the way these risks are approached.'--BOOK JACKET.
Previous ed.(i.e. Rev. ed.): / Institution of Civil Engineers and the Faculty and Institute of Actuaries. 2002.
Includes bibliographical references and index.
Keywords: Capital investments; Risk management; Risk assessment